On the ethics of medical tourism: An examination of patients' perspectives - Sarwar, Abdullah Al-Mamun; Yong Gun Fie, David; Mhd. Sarif, Suhaimi; Nikhashemi, Seyed Rajab (Tehran University of Medical Sciences, 2016)
Medical tourism is often referred to as the act of leaving one’s country to go to a country other than the home country for specific and enhanced medical care and recuperation (1). It represents the less costly private medical care for patients,mostly from developed countries that need serious surgical operations (2). Besides, many patients from less developed countries also visiting various European countries and the United States for better healthcare for some specific diagnostics and treatments which are not available in their own countries (3). Today, medical tourism is truly a global phenomenon. It is being promoted by many countries around the world; owing to the fact that the idea provides these individuals with many benefits. As for the health travelers, there are numerous options for medical vacation spots which add to their advantages and reduced healthcare costs (4). Consequently, medical tourism is not only practical but also economical for those who look to having a satisfying vacation whilst attending to their healthcare needs at the same time. For organizations and administration, medical vacation can be considered as a profitable industry to raise profit and contribute to the gross domestic product.